Burden in Tunisian Family Caregivers of Older Patients with Schizophrenia Spectrum and Bipolar Disorders; Associations with Depression, Anxiety, Stress, and Quality of Life. Issue 5 (2nd September 2020) - Fekih-Romdhane, Feten; Ben Ali, Sana; Ghazouani, Nada; Tira, Salma; Cheour, Majda
ABSTRACT: Background: There are very little data on the burden among caregivers of older adults with severe mental diseases. We aimed to assess the perceived burden among caregivers of family members with schizophrenia spectrum and bipolar disorders. Method: A cross-sectional study was carried out with 52 older patients with schizophrenia spectrum and bipolar disorders and their family caregivers. Caregivers were assessed with the medical outcome survey short form (SF-36), the Zarit Burden Interview (ZBI) and the Depression Anxiety and Stress scales (DASS-21). Results: Caregivers' mental quality of life was impaired with an average mental score of 59.05. For a threshold value of 17, the level of perceived burden was considered as high for 42.3% of caregivers. After controlling for demographic variables (age and gender) and patients' health-related variables (level of dependency, comorbidities, age onset of illness, number of hospitalizations and duration of clinical remission), caregivers' levels of depression, stress, and SF-36 physical component significantly contributed to their perceived burden. Conclusions: Certain modifiable risk factors play an inescapable role in increasing the level of burden among caregivers of older patients with serious mental illnesses. Clinical Implications: Improving the quality of life and psychological well-being of family caregivers should be considered an integral part of treatment for serious mental illness in older adult patients.